OPTIMIZATION OF CADRE PERFORMANCE AND SKILLS TOWARD ACHIEVING HYPERTENSION SCREENING TARGETS AT TELUK BELITUNG COMMUNITY HEALTH CENTER - Despitasary Despitasary; Kiswanto Kiswanto; Apriadi Saputra; Kamali Zaman (HEARTY, 2026)
The low coverage of hypertension screening in the working area of the Teluk Belitung Community Health Center poses a serious challenge in controlling Non Communicable Diseases, with data showing that routine community participation is only 36.5%. This study aims to analyze the low coverage of hypertension screening and to formulate strategies for optimizing the performance of health cadres as the frontline of early detection in the community. Using a qualitative approach with a descriptive design, data were collected through in depth interviews, observations, and document review. Data were analyzed using the Urgency, Seriousness, Growth method to determine problem priorities and SWOT analysis for strategy formulation. The results of the Urgency, Seriousness, Growth analysis identified that suboptimal cadre skills were the main root problem with the highest priority score of 15. Based on the SWOT matrix, this study recommends intervention strategies in the form of transforming guidance methods through a peer-coaching system (Core Cadres) supported by Health Operational Assistance, intensification of outreach services (Mobile Integrated Health Posts), integration of services into community socio cultural activities, and strengthening cross sectoral advocacy to obtain village level regulatory support and village funding. This strategy is expected to change the paradigm of cadre development from a centralized approach to community empowerment supported by local policies as a fundamental step to ensure program sustainability and the achievement of Minimum Service Standard targets in hypertension control.